PERSEPSI KLIEN TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN LAYANAN RAWAT JALAN DI PUSKESMAS KLABANG KABUPATEN BONDOWOSO - Maghfiroh, Wilda (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Health services is most closely related to when someone needs health services and how far the effectiveness of these services. This study aims to analyze the factors that influence clients in utilizing outpatient services at Klabang Community Health Center, Bondowoso District. Quantitative research design with a Cross. With a sample of 245 respondents taken with accidental sampling technique. The tool used was a questionnaire, which then carried out a bivariate and multivariate analysis to determine the factors that influence the client in the use of outpatient services at the Klabang Community Health Center in Bondowoso district. The results of the statistic test found that service facilities, nurse or midwife services, service fees, doctor services, ease of information and health insurance regulation systems significantly affected the utilization of outpatient services. Community perceptions of good service from the community health center give a deep impression and cause motivation to be able to take advantage of the health services provided. If the public knows that service delivery is by what is expected, trust and satisfaction will increase. The Public Health Center as one type of first-level health service facility has an important role in the national health system, specifically the health efforts subsystem.